Intellectual Property Protection of Traditional Cultural Expressions - Li, Luo. author. aut Link
XXIV, 231 p. 11 illus., 9 illus. in color.
Keywords: The work reviews issues concerning the protection of folklore through the intellectual property legal system, then explores two main issues in the protection of Chinese folklore. The first issue is the influence of Chinese traditional culture on the Chinese intellectual property legal system and Chinese society. The second concerns the deficiencies of the Chinese intellectual property system with regard to folklore. Both issues are examined through a survey on the weak public recognition of intellectual property law and folklore in Chinese society. The book also reveals the practical issues that have arisen in Southwest China through case studies. After analysing these issues, the work designs a model law specifically for folklore and also provides suggestions for how the current intellectual property legal system could establish a comprehensive legal protection system for folklore. Furthermore, the work shows that its proposed model law is effective in practice by resolving the issues in the case studies presented.